The effectiveness of clove oil, its fractions, and clove oil-based fumigant tablet formulations, against Tribolium castaneum (Herbst) - Trijanti Anughrahiyaharti Widinni Asnan; Sri Widayanti; Idham Sakti Harahap; Herni Widhisatuti (Perhimpunan Entomologi Indonesia, 2021)
Indonesia has seen an increase and widespread reports of resistance among stored-product insect pests to phosphine. The use of Syzigium aromaticum (clove oil) as an alternative fumigant may be a useful strategy to control infestation by phosphine-resistant varieties of stored-product insects. The objective of this study was to examine the effectiveness of whole (unfractionated) clove oil as well as its component fractions as a fumigant and repellent against the red flour beetle (Tribolium castaneum (Herbst)), and to develop a simple fumigant formulation for this purpose. The experimental design used to test the effectiveness of clove oil and its fractionation was a completely randomized design (CRD). Meanwhile, testing the effectiveness of tablet formulations was carried out by factorial CRD. Fumigation test results gave LD50 and LD95 values of 0.234 and 1.142 ml/l respectively, for crude clove oil used in a fumigation chamber against T. castaneum. An n-hexane fraction of clove oil tested under the same conditions was more lethal, causing 95% mortality of T. castaneum at the dose of 0.801 ml/l during fumigation. Finally, tablets containing a set proportion of clove oil and naphthalene (1:1) reached LD91 against T. castaneum after 7 days’ fumigation.